Frailty in elderly people - Benchimol, Javier A. (Revista del Hospital Italiano de Buenos Aires, 2014)
Frailty is a very important geriatric syndrome by the impact that diagnosis has in the elderly population and adverse health outcomes. The diagnosis is clinical (loss weight, fatigue, muscle weakness, slowed gait and poor physical activity), multifactorial treatment and its early approach allows to improve the quality of life in patients and reduce the costs of care
Keywords: sarcopenia; frailty; vulnerability; disability; elderly